Pendampingan dalam Meningkatkan Kesadaran Masyarakat Desa Cikeleng tentang Pentingnya Pendidikan di Era Digital - Mulyana, Nanang; Saefullah, Rizal; Muzdalifah, Ami; Aprilyani, Tiara; Azizah, Dinda Nur (Lembaga Penelitian, Publikasi Ilmiah dan Pengabdian kepada Masyarakat (LP3M), 2024)
Abstract: Real work lectures (KKN) are a service program organized by universities. The Tridharma of Higher Education regulates universities to care about solving problems in the community, including through community service activities. UM Kuningan Real Work Lecture (KKN) is a community service model that focuses on family empowerment in education, health, entrepreneurship, and environmental aspects. Education is an important aspect to change the attitude of maturity and awareness of students through teaching, training, methods, processes, and educational deeds. In facing life in the digital age.